KORELASI ANTARA FENOMENA SOSIAL DAN FIQH DALAM SISTEM HUKUM POSITIF - Muhsin, Agus (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
Efforts ijtihad actually introduced since the early days of its formation by the Prophet. This step is a friend and inspiration to the next generation to continue to innovate in the field of Islamic jurisprudence. Current social reality, Muslims are faced with a variety of challenges and new problems that require dynamic ijtihad in addressing the social aspects of the Muslim community , as a result of the advancement of science and technology , in order to remain able to meet the challenges of the times that keep rolling with problem - probloma that impose legal settlement . But even so, there also tends to flow more closed to the possibility of the amendments made in the law of Islam, though with through ijtihad. For these circles, understand that all the provisions in Islam, everything is completely presented in the Qur'an qath'iy. Islamic law as a social engginering (social engineering), is a dynamic and creative force in anticipation of any changes and new issues. It can be seen from the emergence of a number of schools syste which has its own style according to sisio-cultural background and political schools of thought in which it is growing and evolving. This phenomenon drove to the system of Islamic law codified law in some Islamic State. Such as found in the familial and social issues (civil). Another aspect of Islamic jurisprudence is still controversial criminal matters (jinayah), recently became a lively issue discussed and fought for codified into the legal system.